DIFFERENT TRANSLATION VERSIONS OF A SHORT STORY: THE PROBLEM OF FIDELITY TO THE ORIGINAL AND ADEQUACY (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores different translation versions of a short story with a focus on the problem of fidelity to the original text and adequacy in translation. The study examines how translators balance the preservation of the source text’s semantic, stylistic, and cultural features with the need to produce a coherent and natural target text. By comparing multiple translations of the same short story, the research identifies variations in lexical choices, syntactic structures, and stylistic strategies.Particular attention is paid to the concepts of fidelity and adequacy, which often function in tension: while fidelity emphasizes closeness to the original, adequacy prioritizes the communicative effectiveness and readability of the translation in the target language. The analysis demonstrates that different translation approaches—ranging from literal to more adaptive strategies—result in diverse interpretative outcomes.
Keywords: translation, fidelity, adequacy, short story translation, translation strategies, equivalence, comparative analysis, literary translation, interpretation, source text, target text